Inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material rich in defects and preparation method and application thereof
The defect-rich anti-opal structure nitrogen and phosphorus-co-doped molybdenum carbide/molybdenum nitride composite material was prepared by the hard template method, which solved the problem of sintering and agglomeration of molybdenum-based catalysts during high-temperature calcination, and achieved efficient hydrogen evolution catalytic performance.
Patent Information
- Application Number
- CN202411861116.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
Existing molybdenum-based catalysts are prone to sintering and agglomeration during high-temperature calcination, resulting in a decrease in active sites, low catalytic activity, and difficult to synthesize and require high temperatures, making it difficult to obtain good nanostructures.
The hard template method is used, with amino-modified silica as the hard template, nitrogen-containing polymer as the carbon source and nitrogen source, and polyoxygenate phosphomolybdate as the phosphorus and molybdenum source. Under the action of the crosslinking agent glutaraldehyde, a phosphomolybdate-loaded polymer-coated silica precursor was prepared by electrostatic binding method, and carbon-carbide-carbide-coated silica composite was prepared at high temperature. Finally, the template was removed by hydrofluoric acid etching to obtain defect-rich anti-opal structure nitrogen, and phosphorus co-doped molybdenum carbide/molybdenum nitride composite.
By creating a large number of defective structures, the active sites of the catalyst are significantly increased, the catalytic activity of the catalyst is improved, the problem of sintering and agglomeration of molybdenum-based catalysts during high-temperature calcination is solved, and efficient hydrogen evolution catalytic performance is obtained.
Smart Images

Figure CN119753737A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrolysis of water for hydrogen evolution and material preparation, and specifically relates to a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material and a preparation method and application thereof. Background Art
[0002] The severe energy crisis and the deteriorating global environment have prompted researchers to focus on the study of sustainable alternative energy sources with abundant natural resources and benign environmental properties. Hydrogen energy is considered to be a promising alternative to carbon-based fuels due to its high energy density and environmental friendliness. Among the existing H2 production pathways (steam reforming, coal gasification, etc.), the electrocatalytic hydrogen evolution reaction (HER) uses renewable clean energy (wind or solar energy) or electricity obtained from oversupplied power grids during off-peak hours. It is the cleanest and most economical way to produce the purest hydrogen. However, in practical applications, HER requires efficient catalysts to overcome large thermodynamic uphill barriers, thereby reducing overpotential and accelerating the reaction rate, resulting in the hydrogen production of this method accounting for only 4% of industrial hydrogen production.
[0003] Pt-based materials have been shown to be the most effective and catalytically stable electrocatalysts for hydrogen evolution reaction, but their high cost and extremely low reserves limit their global application. Therefore, the search for platinum-like electrocatalytically active materials has attracted the attention of many researchers.
[0004] Molybdenum-based catalysts have attracted more and more attention as hydrogen evolution catalysts because of their d-band electronic structure similar to that of platinum and their abundant crustal reserves. In particular, molybdenum carbide (Mo2C) and molybdenum nitride (Mo2N) are currently the most widely used molybdenum-based catalysts in the field of electrocatalysis because of their good conductivity and catalytic activity. However, since the synthesis of Mo2C or Mo2N is usually performed at a relatively high temperature, it is difficult to obtain a good nanostructure. In particular, the synthesis of Mo2N often requires the use of ammonia as a nitrogen source, which is difficult to synthesize. Moreover, during the high-temperature pyrolysis process, the nanostructure will inevitably undergo sintering and agglomeration, resulting in a large reduction in the number of highly active sites in the catalyst. Therefore, at present, molybdenum-based catalysts still cannot achieve high hydrogen evolution catalytic performance. Although agglomeration and sintering can be effectively avoided by loading on a carrier, most traditional carbon materials have a small specific surface area and can provide few loading sites, which cannot give full play to the advantages of the carrier. Summary of the invention
[0005] The purpose of the present invention is to provide a defect-rich inverse opal structure nitrogen, phosphorus co-doped molybdenum carbide / molybdenum nitride composite material and a preparation method thereof. The defect-rich inverse opal structure nitrogen, phosphorus co-doped molybdenum carbide / molybdenum nitride composite catalyst N,P-Mo2C / Mo2N prepared by the present invention has a rich pore structure, and a large amount of molybdenum carbide and molybdenum nitride composites provide a large number of active sites. Moreover, the present invention greatly increases the activity of the active sites of the catalyst by creating a large number of defects in the catalyst. The problems of high-temperature calcination, sintering, agglomeration, limited active sites and low catalytic activity of molybdenum-based catalysts are improved.
[0006] Another object of the present invention is to provide an application of a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material as a catalyst for catalytic hydrogen evolution.
[0007] The specific technical solutions of the present invention are as follows:
[0008] A method for preparing a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material, specifically comprising: using amino-modified silica as a hard template, a nitrogen-containing polymer as a carbon source and a nitrogen source, and polyoxometalate phosphomolybdic acid as a phosphorus source and a molybdenum source, under the action of a cross-linking agent, using an electrostatic bonding method to obtain a phosphomolybdic acid-loaded polymer-coated silica precursor, high-temperature pyrolysis to obtain a carbon-loaded molybdenum carbide / molybdenum nitride-coated silica composite, and then etching to remove the template to obtain a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material.
[0009] The amino-modified silica is NH2-SiO2;
[0010] The amino-modified silica is: 100-200nm silica nanospheres, which are modified by 3-aminopropyltrimethoxysilane (KH-540) in a mixed solution of ethanol and water to obtain NH2-SiO2.
[0011] Preferably, the preparation method of the amino-modified silica is as follows: SiO2 microspheres are dispersed in a mixed solution of ethanol and water, KH-540 is added, and the mixture is heated and stirred to obtain the obtained product.
[0012] More preferably, the preparation method of the amino-modified silica is as follows: 1-2 g of SiO2 microspheres are uniformly dispersed in 100 mL of a 50% ethanol-water mixed solution, 5-10 ml of KH-540 is added, stirred at 60-80° C. for 6-8 h, centrifuged at 8000 rpm for 10-15 min, and washed with deionized water 3 times, and the obtained white product is dried in an oven at 60° C. for 6 h to obtain amino-modified silica NH2-SiO2 nanospheres;
[0013] The preparation method of the SiO2 microspheres is as follows: 10-100 mL of anhydrous ethanol is mixed with 1-10 mL of deionized water and 1-4.5 mL of ammonia water, and then 1-100 mL of tetraethyl silicate (TEOS) is added dropwise to the mixture, reacting at room temperature for 1-2 hours, centrifuging at 25° C. and 8000 rpm for 10-15 minutes to obtain a solid product, washing with deionized water, and drying at 60° C. to obtain silica microspheres SiO2;
[0014] The preparation method of the phosphomolybdic acid-loaded polymer-coated silica precursor is as follows: amino-modified silica is dispersed in ethanol, and solution A is formed by ultrasonic homogeneity; a nitrogen-containing polymer is dissolved in an acetic acid aqueous solution with a volume fraction of 2% to form solution B; polyoxometalate phosphomolybdic acid is ultrasonically dispersed in ethanol to form solution C; solution B and solution A are mixed and stirred uniformly under magnetic stirring conditions, and then solution C is dropwise added to the mixed solution of solution A and solution B, and after stirring, a crosslinking agent aqueous solution with a volume concentration of 5% is added thereto, stirred at room temperature, centrifuged, washed, and vacuum dried to obtain the phosphomolybdic acid-loaded polymer-coated silica precursor;
[0015] The mass ratio of the amino-modified silica, the nitrogen-containing polymer and the polyoxometalate phosphomolybdic acid is: 0.1-0.2: 0.01-0.1: 0.05-0.15;
[0016] Preferably, the phosphomolybdic acid-loaded polymer-coated silica precursor is: 0.1-0.2g of NH2-SiO2 nanospheres are dispersed in 30-50mL of ethanol, and ultrasonically uniformly formed into solution A; 0.01-0.1g of nitrogen-containing polymer is dissolved in 30-50mL of 2% acetic acid aqueous solution to form solution B; 0.05-0.15g of polyoxometalate phosphomolybdic acid is ultrasonically dispersed in 5-20mL of ethanol to form solution C; under magnetic stirring conditions, solution B and solution A are mixed and stirred uniformly, and then solution C is dropwise added to the mixed solution of solution A and solution B, and after stirring for 5-10min, 1-2mL of 5% crosslinking agent aqueous solution is added thereto; stirring at room temperature for 3h, centrifuging to collect the solid, washing with water 3 times, and vacuum drying to obtain the phosphomolybdic acid-loaded polymer-coated silica precursor;
[0017] The nitrogen-containing polymer is any one of chitosan (CS), dopamine (DA), polyethyleneimine (PEI), and aniline (PANI);
[0018] The polyoxometalate phosphomolybdic acid is a Keggin type polyoxometalate H3PMo 12 O 40 ·xH2O is PMo 12 ;
[0019] The cross-linking agent is glutaraldehyde;
[0020] The phosphomolybdic acid loaded polymer coated silica precursor is phosphomolybdic acid loaded chitosan coated silica PMo 12 @CS@SiO2, phosphomolybdic acid loaded dopamine coated silica PMo 12 @PDA@SiO2, phosphomolybdic acid loaded polyethyleneimine coated silica PMo 12 @PEI@SiO2, phosphomolybdic acid loaded polyaniline coated silica PMo 12 @PANI@SiO2 any one;
[0021] The high temperature pyrolysis refers to keeping the temperature at 700-900°C for 2h in a hydrogen / argon mixed atmosphere with a hydrogen volume content of 5%;
[0022] Preferably, the high temperature pyrolysis is as follows: placing the phosphomolybdic acid-loaded polymer-coated silica precursor in a porcelain boat, heating to 700-900° C. at a rate of 5° C. / min in a 5% hydrogen / argon mixed atmosphere, and keeping the temperature for 2 hours to obtain a carbon-loaded molybdenum carbide / molybdenum nitride-coated silica composite;
[0023] The etching refers to etching with a hydrofluoric acid aqueous solution having a volume concentration of 1-5% at room temperature for 1-5 minutes;
[0024] Preferably, the etching is specifically as follows: immersing the carbon-supported molybdenum carbide / molybdenum nitride coated silicon dioxide composite in a 1-5% hydrofluoric acid aqueous solution to etch away the template SiO2 to obtain a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material.
[0025] The defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material is N,P-Mo2C / Mo2N-IOL;
[0026] More preferably, the method for preparing the defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material comprises the following steps:
[0027] 1) Mix 10-100 mL of anhydrous ethanol, 1-10 mL of deionized water, and 1-4.5 mL of aqueous ammonia, then drop 1-100 mL of tetraethyl silicate (TEOS) into the mixture, react at room temperature for 1-2 hours, centrifuge at 25° C. and 8000 rpm for 10-15 minutes to obtain a solid product, wash with deionized water, and dry at 60° C. to obtain silica microspheres SiO2;
[0028] 2) 1-2 g of silica microspheres SiO2 were uniformly dispersed in 100 mL of a 50% ethanol-water mixed solution, 5-10 ml of KH-540 was added, stirred at 60-80 ° C for 6-8 h, centrifuged at 8000 rpm for 10-15 min, and washed with deionized water 3 times. The obtained white product was dried in an oven at 60 ° C for 6 h to obtain amino-modified silica NH2-SiO2 nanospheres;
[0029] 3) Disperse 0.1-0.2g of NH2-SiO2 nanospheres in 30-50mL of ethanol and homogenize by ultrasound to form solution A; dissolve 0.01-0.1g of nitrogen-containing polymer in 30-50mL of 2% acetic acid aqueous solution to form solution B; 0.05-0.15g of PMo 12 Ultrasonic dispersion in 5-20 mL of ethanol to form solution C; under magnetic stirring, solution B and solution A are mixed and stirred evenly, then solution C is added dropwise to the mixed solution of solution A and solution B, after stirring for 5-10 minutes, 1-2 mL of 5% glutaraldehyde aqueous solution is added thereto, stirred at room temperature for 3 hours, solids are collected by centrifugation, washed with water 3 times, and vacuum dried to obtain a phosphomolybdic acid-loaded polymer-encapsulated silica precursor;
[0030] 4) taking 0.1-0.4 g of the obtained precursor phosphomolybdic acid-loaded polymer-coated silica and placing it in a porcelain boat, heating it to 700-900° C. at a rate of 5° C. / min in a 5% hydrogen / argon mixed atmosphere, and keeping it warm for 2 h to obtain a carbon-loaded molybdenum carbide / molybdenum nitride-coated silica composite;
[0031] 5) The carbon-supported molybdenum carbide / molybdenum nitride coated silica composite is immersed in a 1-5% hydrofluoric acid aqueous solution to etch away the template SiO2, thereby obtaining a nitrogen- and phosphorus-doped molybdenum carbide / molybdenum nitride composite catalyst N,P-Mo2C / Mo2N-IOL with a defect-rich inverse opal structure.
[0032] The invention provides a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material, which is prepared by the above method.
[0033] The invention provides an application of a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material as a catalyst in hydrogen evolution by electrolysis of water.
[0034] The present invention aims to solve the problems of high temperature calcination, sintering, agglomeration, limited active sites and low catalytic activity of current molybdenum-based catalysts, and provides a defect-rich inverse opal structure N, P-Mo2C / Mo2N composite catalyst, which has a rich pore structure and a large number of molybdenum carbide and molybdenum nitride composites, providing a large number of active sites. Moreover, the present invention greatly increases the activity of the active sites of the catalyst by creating a large number of defects in the catalyst. The principle of the present invention is as follows:
[0035] The active center of the catalyst prepared by the present invention is defect-rich Mo2C / Mo2N. Compared with pure components of Mo2C and Mo2N, the coupled two-species catalyst shows higher catalytic performance, and due to the presence of a large number of defect sites, the inherent catalytic activity of the active center of the catalyst is greatly improved; moreover, the formation of the Mo2N component in the catalyst of the present invention does not provide an additional nitrogen source, but utilizes the rich nitrogen-containing groups in the nitrogen-containing polymer, simplifies the synthesis process, reduces environmental pollution, and at the same time, the nitrogen atoms in the nitrogen-containing polymer are also doped into the carbon layer at high temperature, thereby improving the conductivity and catalytic performance of the catalyst; in addition, the present invention utilizes NH2-SiO2 microspheres as a hard template and glutaraldehyde as a cross-linking agent, so that the template and the polymer are not simply physically mixed, but there are a large number of chemical bonds, so that in the subsequent process of removing the template, a porous inverse opal structure is formed, and a large number of defect sites are generated, thereby increasing the catalytic activity of the catalyst; the present invention selects PMo 12 As a molybdenum source, it guarantees the uniformity of the molybdenum source to a great extent. At the same time, through electrostatic action, PMo 12 It will be anchored in the macromolecular grid of the nitrogen-containing polymer and the surface of the NH2-SiO2 microspheres. In the subsequent carbonization process, the dispersion and uniformity of the active centers are guaranteed to the greatest extent. 12 The phosphorus atoms in the catalyst will be doped as heteroatoms, participating in regulating the energy band structure of the active center and improving the catalytic hydrogen evolution performance.
[0036] Compared with the prior art, the present invention adopts a hard template method, with amino-modified silica as a hard template, a nitrogen-containing polymer as a carbon source and a nitrogen source, and polyoxometalate phosphomolybdic acid as a phosphorus source and a molybdenum source. Under the action of a cross-linking agent, glutaraldehyde is used, and an electrostatic bonding method is used to confine polyoxometalate phosphomolybdic acid with a uniform size (~1 nm) to the molecular grid of the polymer and the surface of the amino-modified silica, so as to prepare a precursor phosphomolybdic acid-loaded polymer-coated silica precursor, and then a carbon-loaded molybdenum carbide / molybdenum nitride-coated silica composite is obtained by high-temperature pyrolysis, and finally the silica template is removed by hydrofluoric acid etching. In this process, since the amino-modified silica will occupy part of the active sites in the carbon thermal process, a large number of defect structures will be formed inside the catalyst during the removal process, thereby obtaining a nitrogen-phosphorus co-doped molybdenum carbide / molybdenum nitride composite catalyst with a defect-rich inverse opal structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the SEM image of the N,P-Mo2C / Mo2N-IOL obtained in Example 1;
[0038] Figure 2 HRTEM image of N,P-Mo2C / Mo2N-IOL obtained in Example 1;
[0039] Figure 3 The XRD spectrum of N,P-Mo2C / Mo2N-IOL obtained in Example 1;
[0040] Figure 4 The LSV curve and corresponding Tafel curve of N,P-Mo2C / Mo2N-IOL obtained in Example 1 in 1M KOH and 0.5M H2SO4 solutions. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0043] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0044] The NH2-SiO2 used in the present invention is prepared according to the reference [N.Chen, QNGong, F.Wang, et al.N-dopedporous carbon-stabilized Pt in hollow nano-TiO2 with enhanced photocatalyticactivity, Int.J.Hydrogen Energy 45(46)(2020)24779-24791.].
[0045] The preparation method of NH2-SiO2 used in the present invention comprises:
[0046] S1. Mix 100 mL of anhydrous ethanol, 10 mL of deionized water and 4.5 mL of aqueous ammonia, then drop 2.4 mL of tetraethyl silicate (TEOS) into the mixture, react at room temperature for 2 hours, centrifuge at 25°C and 8000 rpm for 15 minutes to obtain a solid product, wash with deionized water, and dry at 60°C to obtain silica microspheres SiO2;
[0047] S2, 2g of SiO2 microspheres were uniformly dispersed in 100mL of 50% ethanol-water mixed solution, 10ml of 3-aminopropyltrimethoxysilane (KH-540) was added, stirred at 80℃ for 6h, centrifuged at 8000rpm for 15min, and washed with deionized water for 3 times. The obtained white product was dried in an oven at 60℃ for 6h to obtain amino-modified silica NH2-SiO2 nanospheres.
[0048] Example 1
[0049] A method for preparing a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material comprises the following steps:
[0050] 1) Preparation of phosphomolybdic acid-loaded chitosan-coated silica precursor, the steps are as follows: 0.15 g NH2-SiO2 was dispersed in 40 mL ethanol by ultrasonic to form solution A; 0.05 g CS was dissolved in 50 mL 2% acetic acid aqueous solution to form solution B, and 0.1 g PMo 12 Ultrasonic dispersion was performed in 10 ml of ethanol to form solution C. Under magnetic stirring, solution A and solution B were uniformly mixed, and then solution C was dripped drop by drop into the mixed solution of solution A and solution B, stirred for 5 min, and 2 mL of 5% glutaraldehyde aqueous solution was added. After stirring at room temperature for 3 h, the solid was collected by centrifugation, washed with water 3 times, and then vacuum dried to obtain a precursor phosphomolybdic acid-loaded polymer-encapsulated silica precursor (PMo 12 / CS@SiO2).
[0051] 2) Preparation of carbon-supported molybdenum carbide / molybdenum nitride-coated silicon dioxide composite, the steps are as follows: 0.3 g PMo 12 The / CS@SiO2 precursor was placed in a porcelain boat and heated to 800°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere and kept at this temperature for 2h to obtain a carbon-supported molybdenum carbide / molybdenum nitride-coated silica composite.
[0052] 3) Preparation of nitrogen, phosphorus-doped molybdenum carbide / molybdenum nitride composite catalysts with defect-rich inverse opal structure, the steps are as follows: the calcined carbon-supported molybdenum carbide / molybdenum nitride-coated silica composite is completely etched with 5 mL of 5% by volume HF aqueous solution for 1 min to obtain a metal carbide (N, P-Mo2C / Mo2N-IOL) with a macroporous inverse opal-like (IOL) structure.
[0053] Figure 1 This is the SEM image of the catalyst N,P-Mo2C / Mo2N-IOL obtained in Example 1; Figure 1 A and B show the SEM images of the prepared catalyst N,P-Mo2C / Mo2N-IOL at different magnifications. Figure 1 Figure A shows a 3D continuous porous structure with an average pore size of ∼200 nm and interconnected nanowalls. Figure 1 The inset in Figure A shows the structure of the catalyst before etching. Figure 1 Figure B shows an enlarged image of the local structure of the prepared catalyst, which clearly shows the macroporous structure in the catalyst and the widely distributed mesopores and micropores on the catalyst surface. These multi-scale pore structures can provide a large specific surface area and expose more catalytic active sites.
[0054] Figure 2 HRTEM image of N,P-Mo2C / Mo2N-IOL obtained in Example 1; Figure 2 The uniformly distributed lattice fringes in the carbon skeleton are clearly shown in the figure, and they can be divided into two crystal phases (Mo2C and Mo2N) according to the different lattice spacings. Mo2C and Mo2N are closely connected (marked by yellow dotted lines), indicating that Mo2C and Mo2N are not mechanical mixtures, but coupled complexes, which will greatly promote the development of the "synergistic effect" of efficient electrocatalysis. Most of the lattice fringes are not continuous (marked by red arrows), indicating the presence of abundant vacancies as point defects, and twin defect structures, lattice distortions and edge dislocations (marked by yellow solid lines) appear in the lattice. The irregular lattice defects greatly improve the intrinsic activity of the active neutral.
[0055] Figure 3This is the XRD spectrum of N,P-Mo2C / Mo2N-IOL obtained in Example 1, which clearly shows the characteristic diffraction peaks of Mo2C (JCPDS#35-0787) and Mo2N (JCPDS#25-1366), further confirming that Mo2C / Mo2N with a clear crystal structure is formed in the composite material.
[0056] Example 2
[0057] A method for preparing a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material comprises the following steps:
[0058] 1) Preparation of phosphomolybdic acid-loaded dopamine-coated silica precursor, the steps are as follows: 0.1 g NH2-SiO2 was dispersed in 30 ml ethanol by ultrasonic to form solution A; 0.1 g DA was dissolved in 30 ml acetic acid aqueous solution with a volume fraction of 2% to form solution B, and 0.15 g PMo 12 Ultrasonic dispersion was performed in 10 mL of ethanol to form solution C. Under magnetic stirring, solution A and solution B were uniformly mixed, and then solution C was dripped drop by drop into the mixed solution of solution A and solution B, stirred for 5 min, and 1.5 mL of 5% glutaraldehyde aqueous solution was added. After stirring at room temperature for 3 h, the solid was collected by centrifugation, washed with water 3 times, and then vacuum dried to obtain a precursor phosphomolybdic acid-loaded polymer-encapsulated silica precursor (PMo 12 / PDA@SiO2).
[0059] 2) Preparation of carbon-supported molybdenum carbide / molybdenum nitride-coated silicon dioxide composite, the steps are as follows: 0.4 g PMo 12 The / PDA@SiO2 precursor was placed in a porcelain boat and heated to 700°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere and kept at this temperature for 2 h to obtain a carbon-supported molybdenum carbide / molybdenum nitride-coated silica composite.
[0060] 3) Preparation of nitrogen, phosphorus-doped molybdenum carbide / molybdenum nitride composite catalysts with defect-rich inverse opal structure, the steps are as follows: the calcined composite is completely etched with 5 mL of 2% HF aqueous solution for 1 min to obtain a metal carbide (N, P-Mo2C / Mo2N-IOL) with a macroporous inverse opal-like (IOL) structure.
[0061] Example 3
[0062] A method for preparing a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material comprises the following steps:
[0063] 1) Preparation of phosphomolybdic acid-loaded polyethyleneimine-coated silica precursor, the steps are as follows: 0.2 g NH2-SiO2 was dispersed in 50 ml ethanol by ultrasonication to form solution A; 0.01 g PEI was dissolved in 40 ml 2% acetic acid aqueous solution to form solution B, and 0.05 g PMo 12 Ultrasonic dispersion was performed in 5 mL of ethanol to form solution C. Under magnetic stirring, solution A and solution B were uniformly mixed, and then solution C was dripped drop by drop into the mixed solution of solution A and solution B, stirred for 5 minutes, and 1 mL of 5% glutaraldehyde aqueous solution was added. After stirring at room temperature for 3 hours, the solid was collected by centrifugation, washed with water 3 times, and then vacuum dried to obtain the precursor phosphomolybdic acid-loaded polymer-coated silica precursor (PMo 12 / PEI@SiO2).
[0064] 2) Preparation of carbon-supported molybdenum carbide / molybdenum nitride-coated silicon dioxide composite, the steps are as follows: 0.2gPMo 12 The / PEI@SiO2 precursor was placed in a porcelain boat and heated to 900°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere and kept at this temperature for 2 h to obtain a carbon-supported molybdenum carbide / molybdenum nitride-coated silica composite.
[0065] 3) Preparation of nitrogen, phosphorus-doped molybdenum carbide / molybdenum nitride composite catalysts with defect-rich inverse opal structure, the steps are as follows: the calcined composite is completely etched with 5 mL of 1% HF aqueous solution for 1 min to obtain a metal carbide (N, P-Mo2C / Mo2N-IOL) with a macroporous inverse opal-like (IOL) structure.
[0066] Example 4
[0067] A method for preparing a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material comprises the following steps:
[0068] 1) Preparation of phosphomolybdic acid-loaded polyaniline-coated silica precursor, the steps are as follows: 0.2 g NH2-SiO2 is dispersed in 40 ml ethanol by ultrasonic to form solution A; 0.1 g aniline is dispersed in 40 ml acetic acid solution with a volume fraction of 2% to form solution B, and 0.1 g PMo 12 Ultrasonic dispersion was performed in 10 ml of ethanol to form solution C. Under magnetic stirring, solution A and solution B were uniformly mixed, and then solution C was dripped drop by drop into the mixed solution of solution A and solution B, stirred for 5 minutes, and 1 ml of 5% glutaraldehyde aqueous solution was added. After stirring at room temperature for 3 hours, the solid was collected by centrifugation and then vacuum dried to obtain the precursor phosphomolybdic acid-loaded polymer-coated silica precursor (PMo 12 / PANI@SiO2).
[0069] 2) Preparation of carbon-supported molybdenum carbide / molybdenum nitride-coated silicon dioxide composite, the steps are as follows: 0.1 g PMo 12 The / PANI@SiO2 precursor was placed in a porcelain boat and heated to 800°C at a rate of 5°C / min in a 5% hydrogen / argon mixed atmosphere and kept at this temperature for 2 h to obtain a carbon-supported molybdenum carbide / molybdenum nitride-coated silica composite.
[0070] 3) Preparation of nitrogen, phosphorus-doped molybdenum carbide / molybdenum nitride composite catalysts with defect-rich inverse opal structure, the steps are as follows: the calcined composite is completely etched with 5 mL of 2% HF aqueous solution for 1 min to obtain a metal carbide (N, P-Mo2C / Mo2N-IOL) with a macroporous inverse opal-like (IOL) structure.
[0071] Example 5
[0072] An application of a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material for catalytic hydrogen evolution, specifically:
[0073] All tests in the present invention were conducted on a Shanghai Chenhua CHI 760E electrochemical workstation, and a three-electrode system was used to evaluate the electrochemical performance of the catalyst, wherein the working electrode used a 3mm glassy carbon electrode modified with a catalyst, the reference electrode was an Ag / AgCl electrode, the counter electrode was a carbon rod, and the electrolyte was 1M KOH and 0.5MH2SO4. The polarization curve of the catalyst was measured by linear sweep voltammetry (LSV) to study the electrochemical hydrogen evolution (HER) performance of the catalyst, wherein the scan rate during the LSV test was 5mV·s -1 The scanning interval was 0.2 to -0.5 V vs RHE, and then the Tafel curve was obtained by converting the LSV curve. The slope of the Tafel curve was used to evaluate the catalyst reaction kinetics.
[0074] Taking Example 1 as an example, the prepared N,P-Mo2C / Mo2N-IOL composite catalyst was tested for LSV in 1M KOH and 0.5MH2SO4 solution, and the LSV curve and the corresponding Tafel curve were plotted. The N,P-Mo2C / Mo2N-IOL catalyst exhibited excellent hydrogen evolution catalytic performance under alkaline conditions. Figure 4 The LSV curve and the corresponding Tafel curve of N,P-Mo2C / Mo2N-IOL obtained in Example 1 in 1M KOH and 0.5M H2SO4 solution are shown in Figure 1. Figure 4As shown in Figure 1, the N,P-Mo2C / Mo2N-IOL catalyst exhibits excellent hydrogen evolution catalytic performance under alkaline conditions, with an initial overpotential of only 25 mV and an overpotential of only 62 mV to reach 10 mA cm -2 Even at a current density of 150 mA cm -2 The catalyst has surpassed the catalytic performance of commercial Pt / C and is superior to other Mo2C / Mo2N-based catalysts reported in alkaline media. This is mainly due to the combined effect of the porous structure and defect structure and the doping of heteroatoms N and P, which weakens the bond energy of Mo-H and enhances the desorption of adsorbed H atoms. Figure 4 Figure B shows that under alkaline conditions, the Tafel slope of the prepared composite catalyst N,P-Mo2C / Mo2N-IOL is 53.8 mV·dec -1 The smaller Tafel slope indicates that the N,P-Mo2C / Mo2N-IOL catalyst has faster hydrogen evolution reaction kinetics, and the hydrogen evolution process should follow the Volmer-Heyrovsky mechanism, with electrochemical desorption as the rate-limiting step. Figure 4 Figures C and D show the catalytic performance of the composite catalyst N, P-Mo2C / Mo2N-IOL in 0.5M H2SO4 solution for hydrogen evolution. Under acidic conditions, the catalyst N, P-Mo2C / Mo2N-IOL also exhibits good hydrogen evolution performance with an initial potential of 34 mV and a current density of 10 mA cm -2 The overpotential is 97 mV and the Tafel slope is 71.1 mV·dec -1 .
[0075] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material, characterized in that: The preparation method comprises the following steps: using amino-modified silica as a hard template, a nitrogen-containing polymer as a carbon source and a nitrogen source, and polyoxometalate phosphomolybdic acid as a phosphorus source and a molybdenum source, obtaining a phosphomolybdic acid-loaded polymer-coated silica precursor by an electrostatic bonding method under the action of a crosslinking agent, performing high-temperature pyrolysis to obtain a carbon-loaded molybdenum carbide / molybdenum nitride-coated silica composite, and then etching to remove the template to obtain a defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material.
2. The preparation method according to claim 1, characterized in that: The amino-modified silicon dioxide is: 100-200nm silicon dioxide nano-microspheres, which are modified by 3-aminopropyltrimethoxysilane in an ethanol-water mixed solution to obtain NH2-SiO2.
3. The preparation method according to claim 1, characterized in that: The preparation method of the phosphomolybdic acid-loaded polymer-coated silica precursor is as follows: amino-modified silica is dispersed in ethanol, and solution A is formed by ultrasonic homogeneity; a nitrogen-containing polymer is dissolved in an acetic acid aqueous solution with a volume fraction of 2% to form solution B; polyoxometalate phosphomolybdic acid is ultrasonically dispersed in ethanol to form solution C; solution B and solution A are mixed and stirred uniformly under magnetic stirring conditions, and then solution C is dropwise added to the mixed solution of solution A and solution B, and after stirring, a crosslinking agent aqueous solution with a volume concentration of 5% is added thereto, the mixture is stirred at room temperature, centrifuged, washed, and vacuum dried to obtain the phosphomolybdic acid-loaded polymer-coated silica precursor.
4. The preparation method according to claim 1 or 3, characterized in that: The mass ratio of the amino-modified silica, the nitrogen-containing polymer and the polyoxometalate phosphomolybdic acid is: 0.1-0.2: 0.01-0.1: 0.05-0.
15.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The nitrogen-containing polymer is any one of chitosan, dopamine, polyethyleneimine, and aniline; the polyoxometalate phosphomolybdic acid is PMo 12 ; The cross-linking agent is glutaraldehyde.
6. The preparation method according to claim 1, characterized in that: The high temperature pyrolysis refers to keeping the temperature at 700-900° C. for 2 hours in a hydrogen / argon mixed atmosphere with a hydrogen volume content of 5%.
7. The preparation method according to claim 1, characterized in that: The etching refers to etching with a hydrofluoric acid aqueous solution having a volume concentration of 1-5% at room temperature for 1-5 minutes.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: 1) Mix 10-100 mL of anhydrous ethanol, 1-10 mL of deionized water, and 1-4.5 mL of aqueous ammonia, then drop 1-100 mL of tetraethyl silicate (TEOS) into the mixture, react at room temperature for 1-2 hours, centrifuge at 25° C. and 8000 rpm for 10-15 minutes to obtain a solid product, wash with deionized water, and dry at 60° C. to obtain silica microspheres SiO2; 2) 1-2 g of silica microspheres SiO2 were uniformly dispersed in 100 mL of a 50% ethanol-water mixed solution, 5-10 ml of 3-aminopropyltrimethoxysilane was added, stirred at 60-80 ° C for 6-8 h, centrifuged at 8000 rpm for 10-15 min, and washed with deionized water 3 times. The obtained white product was dried in an oven at 60 ° C for 6 h to obtain amino-modified silica NH2-SiO2 nanospheres; 3) Disperse 0.1-0.2g of NH2-SiO2 nanospheres in 30-50mL of ethanol and homogenize by ultrasound to form solution A; dissolve 0.01-0.1g of nitrogen-containing polymer in 30-50mL of 2% acetic acid aqueous solution to form solution B; 0.05-0.15g of PMo 12 Ultrasonic dispersion in 5-20 mL of ethanol to form solution C; under magnetic stirring, solution B and solution A are mixed and stirred evenly, then solution C is added dropwise to the mixed solution of solution A and solution B, after stirring for 5-10 minutes, 1-2 mL of 5% glutaraldehyde aqueous solution is added thereto, stirred at room temperature for 3 hours, solids are collected by centrifugation, washed with water 3 times, and vacuum dried to obtain a phosphomolybdic acid-loaded polymer-encapsulated silica precursor; 4) taking 0.1-0.4 g of the obtained precursor phosphomolybdic acid-loaded polymer-coated silica and placing it in a porcelain boat, heating it to 700-900° C. at a rate of 5° C. / min in a 5% hydrogen / argon mixed atmosphere, and keeping it warm for 2 h to obtain a carbon-loaded molybdenum carbide / molybdenum nitride-coated silica composite; 5) The carbon-supported molybdenum carbide / molybdenum nitride coated silica composite is immersed in a 1-5% hydrofluoric acid aqueous solution to etch away the template SiO2, thereby obtaining a nitrogen- and phosphorus-doped molybdenum carbide / molybdenum nitride composite catalyst N,P-Mo2C / Mo2N-IOL with a defect-rich inverse opal structure.
9. A defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the defect-rich inverse opal structure nitrogen and phosphorus co-doped molybdenum carbide / molybdenum nitride composite material according to claim 9, characterized in that: Application in hydrogen evolution by water electrolysis.